Case Report: Pharmacokinetics of ceftazidime and avibactam during and after CRRT in an elderly patient and their associations with CNS adverse effects - Huang, Haiying; Han, Yun; Wu, Yinshan; Guo, Feng; Yu, Zhenwei (Frontiers in Pharmacology, 2025)
Ceftazidime/avibactam is effective for treating infections caused by multidrug-resistant gram-negative bacteria and is widely used. The pharmacokinetic data of ceftazidime and avibactam in patients receiving continuous renal replacement therapy (CRRT) are limited. It is challenging to dose ceftazidime/avibactam, as excessive exposure is associated with central nervous system (CNS) adverse events, especially in older patients. This case reported the pharmacokinetic parameters of ceftazidime and avibactam (1.25 g every 8 h) in an elderly patient during and after CRRT (continuous veno venous hemofiltration mode), which were estimated based on a first-order elimination equation and a two-point sampling strategy. CRRT accounted for 84.9% of the total clearance rate of ceftazidime and 77.1% of the total clearance rate of avibactam. Excessive drug exposure (plasma concentrations of ceftazidime and avibactam were 109 and 20.6 mg/L, respectively) 5 days after discontinuation of CRRT resulted in adverse CNS reactions, which manifested as involuntary convulsions and abnormal brain discharge. This case study provides pharmacokinetic data of ceftazidime and avibactam in patient during and after CRRT and information about the possible relationship between concentrations and CNS adverse reactions.